Water Quality Compatibility of Vaname Shrimp Ponds in PT Solusi Masyarakat Mandiri, Sumbawa Besar, West Nusa Tenggara - m_solihin, m_solihin m_solihin; Dwi Mardhia, Dwi Mardhia Dwi Mardhia; Syamsul Bahri, Syamsul Bahri Syamsul Bahri; Neri Kautsari, Neri Kautsari Neri Kautsari; Yudi Ahdiansyah, Yudi Ahdiansyah Yudi Ahdiansyah (Jurnal Sains dan Teknologi Perikanan, 2025)
Suitability of water quality in cultivating vannamei shrimp is an illustration of water quality to maintain the condition and performance of cultivated shrimp. Water quality standards are an ideal reference for cultivation water quality conditions so that they can increase crop production results. This research aims to analyze the suitability of water quality in the vannamei shrimp ponds of PT Solusi Masyarakat Mandiri, Sumbawa Besar, West Nusa Tenggara. The method used is a survey method with descriptive quantitative data analysis. Measurements of water quality parameters were carried out in two pond plots, namely plots A1 and B7, with the parameters observed including temperature, brightness, pH, salinity, dissolved oxygen, ammonia, nitrate, nitrite and alkalinity. The results of water quality research in plot A1: temperature (30.90c), brightness (34.25 cm), pH (8), salinity (19.72 ppt), dissolved oxygen (5.65 mg/l), ammonia (1 mg/l), nitrite (0.1 mg/l) nitrate (1 mg/l), alkalinity (159 mg/l) are in accordance with SOP and SNI standards except for the amonia and alkalinity parameters. The water quality in plot B7: temperature (30.50c), brightness (57,5 cm), pH (7,85), salinity (46,5 ppt), dissolved oxygen (5.65 mg/l), ammonia (1 mg/l), nitrite (5 mg/l) nitrate (2 mg/l), alkalinity (171 mg/l) showed different results because there were discrepancies with standards for the parameters of brightness, salinity, amonia, nitrate, nitrite and alkalinity. Therefore, optimal water quality management is needed to increase the productivity and survival of vannamei shrimp in ponds.